Trypanosoma cruzi Intracellular Amastigotes Isolated by Nitrogen Decompression Are Capable of Endocytosis and Cargo Storage in Reservosomes - Batista, Cassiano Martin; Kessler, Rafael Luis; Eger, Iriane; Soares, Maurilio José (PLOS ONE, 2015)
Epimastigote forms of Trypanosoma cruzi (the etiologic agent of Chagas disease) internalize and store extracellular macromolecules in lysosome-related organelles (LROs) called reservosomes, which are positive for the cysteine protease cruzipain. Despite the importance of endocytosis for cell proliferation, macromolecule internalization remains poorly understood in the most clinically relevant proliferative form, the intracellular amastigotes found in mammalian hosts. The main obstacle was the lack of a simple method to isolate viable intracellular amastigotes from host cells. In this work we describe the fast and efficient isolation of viable intracellular amastigotes by nitrogen decompression (cavitation), which allowed the analysis of amastigote endocytosis, with direct visualization of internalized cargo inside the cells. The method routinely yielded 5x107 amastigotes—with typical shape and positive for the amastigote marker Ssp4—from 5x106 infected Vero cells (48h post-infection). We could visualize the endocytosis of fluorescently-labeled transferrin and albumin by isolated intracellular amastigotes using immunofluorescence microscopy; however, only transferrin endocytosis was detected by flow cytometry (and was also analyzed by western blotting), suggesting that amastigotes internalized relatively low levels of albumin. Transferrin binding to the surface of amastigotes (at 4°C) and its uptake (at 37°C) were confirmed by binding dissociation assays using acetic acid. Importantly, both transferrin and albumin co-localized with cruzipain in amastigote LROs. Our data show that isolated T. cruzi intracellular amastigotes actively ingest macromolecules from the environment and store them in cruzipain-positive LROs functionally related to epimastigote reservosomes.